An interdisciplinary approach to identify zones vulnerable to earthquakes - Izquierdo-Horna L. (2020)
Earthquakes in Peru are responsible for enormous material and human losses. One of the reasons for the latter is that risk and disaster management policies do not consider individuals as a significant factor for planning post-disaster activities. An understanding of all-important aspects that influence post-disaster efforts would reduce the number of dead, injured and affected people as well as the required money and time to invest. This research develops an interdisciplinary approach, based on seismic vulnerability, to identify those zones that need immediate attention after an earthquake. We consider vulnerability to be a result of two dimensions: social and physical. The first describes society by its anthropogenic characteristics through social indicators (age, daily income, education, etc.). The second describes the built environment and the main features of infrastructure. The results show that the physical and social dimensions intersect and interact with fairly consistent regularity. Thus, we are then able to more accurately identify the areas that require higher prioritization in an emergency scenario. Having this data available for regions predisposed to earthquakes will allow for substantial improvements to current risk mitigation action plans as well as the promotion of a more comprehensive prevention effort.